2003
DOI: 10.1093/humrep/deg184
|View full text |Cite
|
Sign up to set email alerts
|

Early cleavage predicts the viability of human embryos in elective single embryo transfer procedures

Abstract: The current study provides compelling evidence that EC embryos possess significantly higher developmental competence than NEC embryos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
90
2
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(111 citation statements)
references
References 39 publications
(57 reference statements)
11
90
2
6
Order By: Relevance
“…The study presented here used exclusively day 5 embryos and clearly demonstrates that acceptable pregnancy rates can be achieved using single embryo transfers in a relatively unselected population of IVF patients. This study confirms those conducted previously (Martikainen et al, 2001;Salumets et al, 2003;Tiitinen et al, 2001;Vilska et al, 1999) using day 3 embryos. Only one study ) has included cumulative pregnancy rate but unfortunately the data did not include the cumulative rate for those patients having two embryos transferred in their stimulated cycle.…”
Section: Discussionsupporting
confidence: 92%
“…The study presented here used exclusively day 5 embryos and clearly demonstrates that acceptable pregnancy rates can be achieved using single embryo transfers in a relatively unselected population of IVF patients. This study confirms those conducted previously (Martikainen et al, 2001;Salumets et al, 2003;Tiitinen et al, 2001;Vilska et al, 1999) using day 3 embryos. Only one study ) has included cumulative pregnancy rate but unfortunately the data did not include the cumulative rate for those patients having two embryos transferred in their stimulated cycle.…”
Section: Discussionsupporting
confidence: 92%
“…Pregnancy rate by transfer of Day 2 embryos in the early cleaving group was significantly higher than that in the late cleaving group (Chi-squared test, P<0.05). The actual percentages are shown within the bars [11,12,17,18]. This study confirmed that embryos that had cleaved by 27 h had significantly higher blastocyst rates than later cleaving embryos.…”
Section: Discussionsupporting
confidence: 67%
“…Both animal and human studies have demonstrated that timely entry into the first cleavage (so called Bearly cleavage^) is associated with developmentally more competent embryos compared with late cleavage or no cleavage [37]. Indeed, embryos that cleave between 24 and 27 h after fertilization are more developmentally competent, resulting in higher blastocyst and implantation rates compared with those that cleave relatively later [7,13,[38][39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%